Estilos de enseñanza en docentes de las instituciones educativas públicas de nivel primaria en Caballococha, Ramón Castilla 2021 - Lopez Oliveira, Maver Lucero (2022)
The general objective of the research was to describe the teaching styles in teachers of public primary level institutions in the city of Caballo Cocha, province of Ramón Castilla in 2021. The type of research is descriptive, with a univariate, cross-sectional design, and field. The population and sample consisted of 192 primary school teachers belonging to the various educational institutions in the area. To obtain reliable and valid data, it was submitted to expert judgment by expert teachers in the area, and the survey technique was used. The research concludes that the level of teaching styles of primary school teachers is 78.1% good: in 13.0% very good and in 8.9% poor in Public Institutions of Primary level in Caballo cocha, province of Ramón Castilla in 2021.